(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Bioethanol production is in high demand due to its potential to replace transportation fuel and its ability to be renewable and long-lasting. Therefore, the bioconversion of fermentable sugars to ethanol is of central importance. The work aimed to explore yeast properties changes during fermentation at different pHs and temperature conditions. Biomass production, specific growth rate (SGR), fermentation products, and metabolite composition and quantity changes were studied at 25℃, 30℃, and 37℃ as well as pH 5 and pH 6.5 conditions. SGR data shows that at 25℃ and 30℃ pH 5 is optimal for yeast biomass production. At pH 5.0–6.5, the biomass production of the ATCC 9804 strain almost 2 times exceeds the same parameter for another strain. The highest biomass production was detected at 30℃ and pH 5. Ethanol production by yeast increases as the growth temperature decreases at pH 5 in contrast to pH 6.5, where the temperature changes within 30–37℃ range have no significant effect on it in both strains. At 30℃ ethanol concentration in the extracellular medium reached 117 mM in the case of ATCC 13007 strain, whereas for ATCC 9804 the same parameter was 1.4-fold lower. Both strains had the same substrate assimilation rate. Glycerol production reduces with increasing growth temperature and pH; the highest glycerol concentration (6.1 mM) was observed within 32 h growth of ATCC 9804 strain at 25℃, pH 5 and reaches 5.5 mM within 24 h growth of ATCC 13007 strain under the same conditions. At pH 5 and 6.5, the free energy for glycerol production was 2.3-fold and 4-fold higher compared to that of ethanol and acetate production processes in both strains. Gibbs free energy of ethanol production reaches the lowest value compared to the same parameter of acetate and glycerol production at pH 5, suggesting a preference for the alcoholic fermentation metabolic pathway under these conditions. The lowest acetate production was observed after 24 hours of growth of the ATCC 13007 strain at 37°C and pH 5, with ΔG = 173.9 kJ/mol. Obtained data highlights temperature stress mechanisms regulation of yeast and can be used for improving ethanol production processes and yeast genetic modification tools.